Gender and development: bridging the gap between research and action - Quisumbing, Agnes R.; McClafferty, Bonnie (International Food Policy Research Institute, 2006)
Practitioners may ask why they should address gender issues in development. Aside from the obvious answer—that gender equality is a basic human right and in that sense is integral to development—many disparities in development outcomes stem from gender differences. While practitioners are often knowledge-able about general development or technical issues, many lack the understanding and resources necessary to effectively integrate gender issues into specific projects and public policy. Further, many practitioners are not convinced of the importance of gender issues, or they may find it difficult to navigate approaches in the context of development.